The Effect of Influencer Marketing, User-Generated Content, And Brand Image on Purchasing Decisions for Skintific Products on Tiktok Shop - Laia, Devi Krisdayanti; Prayogo, Rangga Restu (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of influencer marketing, user generated content, and brand image on purchasing decisions for skintific products in the TikTok shop. The method used is quantitative descriptive with non-probability sampling and accidental sampling techniques, involving 68 respondents in the 2021 management department at the State University of Medan who use TikTok and have used skintific products. Data collection was carried out through observation and distributing questionnaires via Google Form, then analyzed using SPSS 30. The results of the study showed that influencer marketing and brand image had a positive and significant effect on purchasing decisions for skintific products in the TikTok shop (p = 0.20 less than 0.05) and (p = 0.001 less than 0.05) While user generated content did not have a significant effect on purchasing decisions for skintific products in the TikTok shop (p = 0.525 more than 0.05). The F test shows that all three variables simultaneously influence purchasing decisions for skintific products in the TikTok shop. This study recommends that further research can add other supporting variables and analyze on other platforms. It is hoped that the results of this study can be a reference for skintific companies in improving consumer purchasing decisions, especially TikTok.